Análisis de la gravedad por COVID -19, Hospital Carlos Andrade Marín, Quito, 2020 - Guerrero Paredes, Darwin Wladimir (2020)
Background: COVID-19 is a respiratory disease that causes a nonspecific clinical char, with symptoms are ranging from the common cold to serious illnesses such as severe acute respiratory syndrome (ARDS) and even death. Over the months, research has not been sufficient to determine a specific treatment for this disease, so the estimation of risk factors, comorbidities and extension laboratories have been of great importance to promote prevention, especially in the different risk groups. Objective: To Analyse the severity of COVID -19 at Carlos Andrade Marín Hospital in Quito, 2020. Material and methods: A descriptive, non-experimental, cross-sectional and retrospective study was carried out, based on the review of medical records of a matrix of 3717 patients with suspicion COVID-19, obtained from the emergency service of the Carlos Andrade Marín Hospital in the period April - July 2020. Results and Conclusions: Using inclusion and exclusion criteria, the sample consisted of 290 patients, predominantly male, older than 60 years. Like 87.58% of the patients, they required hospital management and with a fatality of 11.03%. The associated chronic pathology was arterial hypertension (48%), followed by diabetes mellitus (31%). Finally, laboratory tests obtained are altered 5 out of 5, helping to foresee a therapeutic behaviour that allows monitoring the patient's condition, its evolution and possible complications.